LncPrep + 96kb 2.2 kb Inhibits Estradiol Secretion From Granulosa Cells by Inducing EDF1 Translocation - Feng, Fen; Wang, Jing; Bao, Riqiang; Li, Long; Tong, Xiating; Han, Suo; Zhang, Hongdan; Wen, Weihui; Xiao, Li; Zhang, Chunping (Frontiers in Cell and Developmental Biology, 2020)
LncPrep+96kb is a novel long noncoding RNA (lncRNA) expressed in murine granulosa cells with two transcripts that are 2.2 kb and 2.8 kb in length. However, the potential roles of lncPrep+96kb in granulosa cells remain poorly understood. In this study, we investigated the effect of the lncPrep+96kb 2.2 kb transcript on granulosa cells through the overexpression and knockdown of lncPrep+96kb 2.2 kb. We found that lncPrep+96kb 2.2 kb inhibited aromatase expression and estradiol production. Endothelial differentiation-related factor 1(EDF1) is an evolutionarily conserved transcriptional coactivator. We found that EDF1 knockdown inhibited aromatase expression and estradiol production. The RNA immunoprecipitation (RIP) results also showed that lncPrep+96kb 2.2 kb can bind to EDF1 and that overexpression of lncPrep+96kb 2.2 kb induced the translocation of EDF1 from the nucleus to the cytoplasm. The CatRAPID signature revealed that the 1979-2077 and 603-690 nucleotide positions in lncPrep+96kb 2.2 kb were potential binding sites for EDF1. We found that mutating the 1979-2077 site rescued the effects of lncPrep+96kb 2.2 kb on aromatase expression and estradiol production. In conclusion, we are the first to report that specific expression of lncPrep+96kb 2.2 kb in granulosa cells inhibits the production of estradiol by influencing the localization of EDF1 in granulosa cells. The 1979-2077 site of lncPrep+96kb 2.2 kb contributes to the ability to bind to EDF1.